IMPLEMENTATION OF OCCUPATIONAL ON TOWER CRANE OPERATION AT PT. PULAUINTAN BAJA PERKASA SURABAYA - Defika Kristika Sari (Universitas Darussalam Gontor, 2018)
During infrastructure construction, various equipments are required to ensure increase in productivity. Example of such equipment is tower crane. But while it eases the work process, it may also cause dire accident, for instance, in 2015 a tower crane collapsed in Masjidil Haram, Mecca. Similar accident also happened during Double Double Track (DDT) construction in Kampung Melayu, claiming 4 workers’ lives. Consequently, tower crane operation requires great deal amount of attention on safety. PT. Pulauintan Baja Perkasa uses tower crane during construction process as a main heavy duty equipment. The aim of this study is to identify implementation of Occupational Safety and Health on tower crane usage on 88 Avenue project according to regulations that apply. This study is using descriptive method and cross sectional approach. Subjects in this study were 1 technician, 6 riggers, and 2 operators in charge of tower crane usage. Object in this study was one tower crane out of three cranes used in the project. Primary and secondary data are analyzed using related regulations and presented using narration.: Result shows that tower crane no.2 was found not qualified due to not accomplishing 15% of Ministerial Regulation No. 05 year 1987 by Ministry of Manpower of the Republic of Indonesia. Both technician and rigger have fulfilled most of ministerial regulations (80%), not yet meeting 15% of Ministerial Regulation No. 09 year 2010. Operators are found to have met aforementioned regulation.From the results, it can be concluded that implementation of OSH on tower crane usage in PT. Pulauintan Baja had some inadequacies. It can be concluded that there are some deficiencies in the application of Occupational Safety and Health in the use of Tower Crane.Keyword: Tower crane, Operator, Officer